Fabrication and characteristics of CH3NH3PbI3 perovskite solar cells with molybdenum-selenide hole-transport layer. (16th November 2016) - Chen, Lung-Chien; Tseng, Zong-Lieng; Chen, Cheng-Chiang; Chang, Sheng Hsiung; Ho, Cheng-Han
Abstract: We present a solar cell with an FTO/MoSe2 /perovskite/C60 /bathocuproine (BCP)/silver structure. The hole-transport material (HTM), active photovoltaic layer, electron-transport layer, and electron-buffer layer were made of MoSe2, perovskite, C60, and BCP, respectively. The domain sizes of the CH3 NH3 PbI3 (MAPbI3 ) perovskite films that were deposited on the MoSe2 HTM films following annealing at 500, 600, and 700 °C were determined to be 23, 25, and 27 nm, respectively, revealing that the domain size of the MAPbI3 perovskite film increased with the annealing temperature of the MoSe2 HTM film under it. Therefore, the crystallinities of the perovskite layers were improved by increasing the annealing temperatures of the HTM layers. Following optimization, the maximum power-conversion efficiency was 8.23%.